Global Bibliometric Analysis of Endophytic Actinomycetes From 2013 to 2023 - Aseptin Murdini, Lia; Al Laitsi, Muawiyatu; Nurkayah, Nurkayah (Jurnal Agrosci, 2024)
Endophytic actinomycetes isolated from surface-sterilized of several plant species. These bacteria are also known as producers of plant growth regulators and hormone synthesizers, innovative resources in plant disease control. The aim of this study is to identify keywords and contributions of authors, countries, and institutions of actinomycetes endophytes research in the world for ten years (2013-2023) from the Scopus database. This research uses the bibliometric analysis method. Data were extracted from the Scopus database with the specified keyword query: Endophytic Actinomycetes using Publish or perish 8. Selected bibliometric details were performed and visualized by VOSviewer. The results from the beginning search of publications were obtained from 170 articles; according to the content, there are 145 articles. The analysis, facilitated by VOSviewer software, focused on 353 keywords with a frequency of 1 or more. All keywords were systematically grouped into 76 clusters. The investigation spans the last decade and identifies the top ten keywords: endophytic actinomycetes, 16S rRNA, Polyphasic Taxonomy, Streptomyces, Antimicrobial activity, Medicinal Plants, Antifungal, Oriza sativa, Plant growth Promoting, Indole-3-Acetic Acid. The most productive author is Liu Chongxi, Followed by Xiang Wencheng. Countries contributing: China, Next Thailand, India, Japan, Vietnam. Institution published, Northeast Agricultural University, Kasetsart University, Chulalongkorn University, Jiangsu Normal University.